A STUDY ON HOW SOCIAL MEDIA RESHAPES THE WAY OF FAMILY COMMUNICATION IN SRI LANKA - Lokumannage, Amila (ASIA PACIFIC INSTITUTE OF ADVANCED RESEARCH, 2021)
This study analyzed how social media reshapes the way of family communication in Sri Lanka. The study had three objectives. Those were to identify which kind of social media platforms use Sri Lankan family members, to study how often Sri Lankan family members communicate with each other’s through social media and to understand how social media affects communication among Sri Lankan family members. The research questions of the study were, 1: Which social media platforms use Sri Lankan family members in difference age groups? How often Sri Lankan family members communicate with each other’s through social media? And 3: Does the social media enable family members in Sri Lanka to connect better with each other? Quantitative survey method used to get the results by 100 respondents (50 children and 50 parents). Participants of the survey were from 18 to 60 years old, of non-specific educational background or social class. The researcher used quantitative techniques with the help of tables, graphs, and charts to analyze the findings of the study. According to the results, 97% of young people use social media platform for their day to day communication. Almost 93% of the respondents have responded that they are in touch with their family members every day through social media.
Keywords: Communication; Social media; Family; Sri Lanka